2019
DOI: 10.1038/s41598-019-50539-9
|View full text |Cite
|
Sign up to set email alerts
|

The Intrinsic Enzyme Activities of the Classic Polyoxometalates

Abstract: The mimicking enzyme activities of eighteen classic POMs with different structures, Keggin (H3PW12O40, H4SiW12O40, H4GeW12O40, K4GeW12O40, H3PMo12O40, H4SiMo12O40 and Eu3PMo12O40), Wells-Dawson (H6P2Mo18O62, α-(NH4)6P2W18O62 and α-K6P2W18O62·14H2O), lacunary-Keggin (Na8H[α-PW9O34], Na10[α-SiW9O34], Na10[α-GeW9O34] and K8[γ-SiW10O36]), the transition-metal substituted-type (α-1,2,3-K6H[SiW9V3O34] and H5PMo10V2O40), sandwich-type (K10P2W18Fe4(H2O)2O68) and an isopolyoxotungstate (Na10H2W12O42) were screened and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…The level of K m and V max obtained for SVW 11 and SV 2 W 10 are highly comparable to pervious findings of various nanostructured materials based nanozymes as shown in (Table 1). [10,14,23,24,[33][34][35][36][37][38][39][40] These results suggest that the POMs exhibit strong affinity towards H 2 O 2 and TMB and possess excellent peroxidase-like activity. A separate set of experiments were set up to compare the catalytic performance of these novel of POMs with standard natural peroxidase horseradish peroxidase (HRP).…”
Section: Peroxidase-like Activity Of Pom Nanomaterialsmentioning
confidence: 77%
See 2 more Smart Citations
“…The level of K m and V max obtained for SVW 11 and SV 2 W 10 are highly comparable to pervious findings of various nanostructured materials based nanozymes as shown in (Table 1). [10,14,23,24,[33][34][35][36][37][38][39][40] These results suggest that the POMs exhibit strong affinity towards H 2 O 2 and TMB and possess excellent peroxidase-like activity. A separate set of experiments were set up to compare the catalytic performance of these novel of POMs with standard natural peroxidase horseradish peroxidase (HRP).…”
Section: Peroxidase-like Activity Of Pom Nanomaterialsmentioning
confidence: 77%
“…POMs have found wide ranging applications in the area of catalysis. [12,14] Additionally, the POMs can be systematically tuned at atomic levels: [15] Removal of one, two or three metal octahedrons from the parent POMs, [XM 12 O 40 ] nÀ (X=S, P, As, Si, Ge; M=W, Mo) by sophisticated pH control results in the formation of mono-, dior tri-lacunary POMs. [16] POM catalysts have many advantages, such as high efficacy, stability and designability, making them promising candidates for industrial catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Thus, POMs can be applied as enzyme mimics to catalyse H 2 O 2based oxidation of 3,3 0 ,5,5 0 -tetramethylbenzidine (TMB). 23 Li et al prepared three tetra-nuclear ZrIV-substituted POMs, which exhibit peroxidase-like activities. 24 It was found that most of the POMs are stable and have more enzyme activities at low pH values (about 3.0 or 4.0).…”
Section: Introductionmentioning
confidence: 99%
“…24 It was found that most of the POMs are stable and have more enzyme activities at low pH values (about 3.0 or 4.0). 23,24 However, it is interesting to develop intrinsic oxidase nanozymes since they do not use harmful H 2 O 2 as a co-substrate.…”
Section: Introductionmentioning
confidence: 99%